Environmental Legal Culture as a Factor in Ensuring Sustainable Development of Society - Kurylo, Liudmyla; Kurylo, Inna; Shulga, Ievgenii; Horodetska, Iryna (European Journal of Sustainable Development, 2020)
The purpose of the article is to clarify the role and importance of environmental legal culture in ensuring the sustainable development of society. Methodological basis of the research includes general theoretical principles of scientific knowledge (comprehensiveness, validity, complexity), which allowed to provide various aspects in the study of ecological legal culture. It is based on a complex combination of research approaches, the leading among which is integrative, as well as general scientific methods (formal-logical, structural and functional). Scientific novelty is to identify the essence and importance of environmental legal culture as one of the main factor for ensuring the sustainable development of society. Based on the analysis of scientific-theoretical approaches of the understanding of environmental culture, legal culture, environmental legal culture, as well as the current legislation and sources devoted to diagnostics of the effectiveness of the implementation of national environmental policy, it is substantiated that environmental legal culture is a complex integral category that includes a complex of interconnected cognitive, value and activity components, characterized by a certain level of environmental and legal knowledge and active activity in their practical reality ted; is a factor in the effectiveness of legal regulation of public relations in the field of environmental protection and an effective instrument of environmental policy in the country, and therefore a factor in ensuring the sustainable development of society. Keywords: environmental culture, legal culture, environmental legal culture, environmental policy, sustainable development.